2022
DOI: 10.3389/fmed.2022.1041668
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired bloodstream infections in patients deceased with COVID-19 in Italy (2020–2021)

Abstract: IntroductionIn hospitalized patients with COVID-19, bloodstream infections (BSI) are associated with high mortality and high antibiotic resistance rates. The aim of this study was to describe BSI etiology, antimicrobial resistance profile and risk factors in a sample of patients deceased with COVID-19 from the Italian National COVID-19 surveillance.MethodsHospital charts of patients who developed BSI during hospitalization were reviewed to describe the causative microorganisms and their antimicrobial susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…An investigation conducted on HA-BSI in patients deceased with COVID-19 in Italy, identified A. baumannii as one of the most frequently isolated pathogens, mainly in ICU, with a 100% of carbapenem resistance profile [ 64 ]. Similar results were confirmed in a retrospective observational study conducted in Greece, showing CR-Ab as the principal cause of Gram-negative BSI [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…An investigation conducted on HA-BSI in patients deceased with COVID-19 in Italy, identified A. baumannii as one of the most frequently isolated pathogens, mainly in ICU, with a 100% of carbapenem resistance profile [ 64 ]. Similar results were confirmed in a retrospective observational study conducted in Greece, showing CR-Ab as the principal cause of Gram-negative BSI [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of those positive blood culture isolates, a higher occurrence of Acinetobacter baumannii , CoNS , Staphylococcus aureus and Enterococcus species was significantly associated with the use of higher corticosteroid doses ( p < 0.05 for all analyses), while the occurrence of Klebsiella pneumoniae isolates was comparable. Acinetobacter baumannii was reported in earlier studies as the most frequent Gram-negative BSI in COVID-19 patients [ 32 , 44 ]. Our findings are very similar to those of Frattari et al, who found that not only was Acinetobacter baumannii the most frequent cause of bacteremia, while preceded colonization was documented in only 7% of cases, but that bacteremia was implied to be hospital-acquired [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are very similar to those of Frattari et al, who found that not only was Acinetobacter baumannii the most frequent cause of bacteremia, while preceded colonization was documented in only 7% of cases, but that bacteremia was implied to be hospital-acquired [ 36 ]. Moreover, the use of corticosteroids was found to be associated with hospital-acquired Acinetobacter baumannii bacteremia, resulting in poorer outcomes, while early administration was associated with increased bacterial resistance [ 44 , 45 ]. These, along with previous findings of an association between high-dose steroids and Acinetobacter bacteremia [ 46 ], support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Such secondary infections, especially secondary invasive fungal infection (IFIs) and bloodstream infections, increased morbidity and mortality of hospitalized COVID-19 patients. 5 , 9 Therefore, the rapid comprehensive identification of the pathogens responsible for the development of secondary infections in COVID-19 patients is essential to implement individually tailored antibiotic therapy, improve antimicrobial stewardship and help prevent emergence and transmission of multi-drug-resistant (MDR) organisms.…”
Section: Introductionmentioning
confidence: 99%